Experimental out-of-plane behavior of brick masonry infilled frames - Akhoundi, Farhad (2020)
The vulnerability of masonry infills within reinforced concrete (rc) frames under out-of-plane loading induced by earthquakes has been observed in several past earthquakes through severe damage and often total collapse. Although the infill panels are assumed as non-structural elements, their damage or collapse is not desirable, given the possible consequences in terms of human life losses and repair or reconstruction costs. Therefore, it is important to gather better insight on the out-of-plane behavior of existing infills so that strengthening guidelines can be derived. In this scope, the main objective of this study is to analyze the out-of-plane experimental behavior of masonry infilled frames that are characteristic of Portuguese buildings and can be seen in other south European countries. In the experimental study carried out, different parameters affecting the out-of-plane response of infilled frames were considered, namely, workmanship, existence of openings and prior in-plane damage. The experimental program was designed to test six half-scale specimens. The out-of-plane loading was applied uniformly to the brick infills by means of an airbag to simulate the effect of earthquakes.